Evaluation of Anatomic Variations in Maxillary Sinus with the Aid of Cone Beam Computed Tomography (CBCT) in a Population in South of Iran - Shahidi, Shoaleh (J Dent (Shiraz), 2016)
STATEMENT OF THE PROBLEM: Anatomic variations of the maxillary sinus can be detected in cone-beam computed tomography (CBCT) and may assist to locate the posterior superior alveolar artery (PSAA) and define the maxillary sinus morphology more accurately for a more strict surgical treatment plan. PURPOSE: The study aimed to determine normal variations of the maxillary sinus with the aid of CBCT in a sample population in south of Iran. MATERIALS AND METHOD: This cross-sectional prevalence study was based on evaluation of 198 projection data of CBCT scans of some Iranian patients aged 18-45 who referred to a private oral and maxillofacial radiology center in Shiraz from 2011 to 2013. CBCT scans were taken and analyzed with NewTom VGi device and software. The anatomic variations which were evaluated in the axial images included the presence of alveolar pneumatization, anterior pneumatization, exostosis, and hypoplasia. Moreover the location and height of sinus septa, and the location of PSAA were assessed. SPSS software (version 17.0) was used to analyze the data. RESULTS: In a total of 396 examined sinuses, maxillary sinus alveolar pneumatization was the most common anatomic variation detected. Anterior pneumatization was detected in 96 sinuses (24.2%). Antral septa were found in 180 sinuses (45.4%) and were mostly located in the anterior region. Meanwhile, PSAA was mostly detected intra-osseous in 242 sinuses (65.7%). CONCLUSION: Anatomic variations of the maxillary sinus were common findings in CBCT of the maxilla. Preoperative imaging with CBCT seems to be very helpful for assessing the location of PSAA and the maxillary sinus morphology, which may be used to adjust the surgical treatment plan to yield more successful treatments.